INFORMATION TECHNOLOGY SECURITY AIRCRAFT FLIGHT IN DIFFICULT CONDITIONS BASED MULTIFACTORIAL FUZZY MODELS - Agayev, Nadir Bafadin oqlu; Agamalieva, Jeyran Aqamali qizi (Proceedings of National Aviation University (archive), 2014)
The proposed method is designed for situations where the original information that characterizes the state of the aircraft, clearly defined and numerical variables and the so-called “linguistic variables” This simple relationship between the variables are described by means of fuzzy statements, and the complex relationship between the concepts with fuzzy algorithms